The Neural Correlates of Grammatical Gender: An fMRI Investigation - Miceli, Gabriele; Turriziani, Patrizia; Caltagirone, Carlo; Capasso, Rita; Tomaiuolo, Francesco; Caramazza, Alfonso (Journal of cognitive neuroscience, 2002)
In an fMRI experiment, subjects saw a written noun and made three distinct decisions in separate sessions: Is its grammatical gender masculine or feminine (grammatical feature task)? Is it an animal or an artifact (semantic task)? Does it contain a /tch/ or a /k/ sound (phonological task)? Relative to the other experimental conditions, the grammatical feature task activated areas of the left middle and inferior frontal gyrus and of the left middle and inferior temporal gyrus. These activations fit in well with neuropsychological studies that document the correlation between left frontal lesions and damage to morphological processes in agrammatism, and the correlation between left temporal lesions and failure to access lexical representations in anomia. Taken together, these data suggest that grammatical gender is processed in a left fronto-temporal network. In addition, the observation that the grammatical feature task and the phonology task activated neighboring but distinct regions of the left frontal lobe provides a plausible neuroanatomical basis for the systematic occurrence of phonological errors in aphasic subjects with morphological deficits.